Endoscopic papillectomy for neoplastic ampullary lesions: A systematic review with pooled analysis. Issue 1 (1st February 2020) - Spadaccini, Marco; Fugazza, Alessandro; Frazzoni, Leonardo; Di Leo, Milena; Auriemma, Francesco; Carrara, Silvia; Maselli, Roberta; Galtieri, Piera Alessia; Chandrasekar, Viveksandeep Thoguluva; Fuccio, Lorenzo; Aljahdli, Emad; Hassan, Cesare; et al.
Abstract : Endoscopic papillectomy (EP) is a viable therapy in ampullary lesions (AL). Many series have reported low morbidity and acceptable outcomes. We performed a systematic review with pooled analysis to assess the safety and efficacy of EP for AL. Electronic databases (Medline, Scopus and EMBASE) were searched up to September 2018. Studies that included patients with endoscopically resected AL were eligible. The rate of adverse events (AEs; primary outcome) and the rates of both technical and clinical efficacy outcomes were pooled by means of a random‐ or fixed‐effects model to obtain a proportion with a 95% confidence interval (CI). Twenty‐nine studies were included (1751 patients). The overall AE rate was 24.9%. The post‐procedural pancreatitis rate was 11.9%, with the only factor affecting this outcome being prophylactic pancreatic stenting. The complete resection rate was 94.2%, with a rate of oncologically curative resection of 87.1%. The recurrence rate was 11.8% (follow‐up: 9.6–84.5 months). EP is a relatively safe and effective option for AL. Our study might definitively suggest the protective role of prophylactic pancreatic stenting against post‐procedural pancreatitis.